Supportive enriched environment improves recovery from persistent motor and cognitive impairments after severe traumatic brain injury - Lovier, Margaret Anne; Kyle, Michele; Hughes, Karen; Zhao, Li-Ru (Frontiers in Behavioral Neuroscience, 2026)
ObjectiveSevere traumatic brain injury (sTBI) causes permanent disability in adults worldwide. While enriched environments (EE) have been shown to improve recovery in the early post-TBI period, their efficacy during the chronic phase of sTBI remains unclear. This study evaluated neurological function recovery in mice with chronic sTBI housed in either traditional EE or supportive EE.MethodsAdult male C57BL mice were subjected to sTBI by controlled cortical impact and maintained in standard environments (SE) for 7 months. sTBI mice were then randomized into SE (TBI-SE), traditional EE (TBI-EE-1), or supportive EE (TBI-EE-2, co-housed with sham mice). Sham controls were housed in SE (Sham-SE) or supportive EE (Sham-EE-2). EE consisted of a large stainless-steel cage with toys replaced three times weekly. Mice remained in these conditions for 10 weeks, and neurobehavioral testing was performed beginning in week 6.ResultsIn the RotaRod test, TBI-SE mice displayed persistent motor coordination and learning deficits, whereas TBI-EE-2 mice showed robust motor coordination recovery and improved motor learning. Of all TBI mice, only the TBI-EE-2 mice demonstrated improved motor learning. In the Morris water maze test, both TBI-EE-1 and TBI-EE-2 groups showed enhanced spatial learning and memory compared with TBI-SE. Y-maze testing revealed impaired short-term memory in TBI-EE-1 mice but significant improvement in TBI-EE-2 mice. Anxiety-like behavior, assessed by open field and light–dark box tests, was reduced only in the TBI-EE-2 mice.ConclusionSupportive EE more effectively reduced anxiety and improved motor and cognitive function in chronic sTBI compared with conventional EE. These findings highlight the potential value of incorporating social integration with healthy individuals into rehabilitation programs to optimize recovery in chronic severe TBI.